PERANCANGAN ALAT PELUBANG PLASTIK KEMASAN TEMPE DENGAN PENDEKATAN ANTHROPOMETRI GUNA MENINGKATKAN PRODUKTIVITAS - Khoirulloh, Abdilah Fajar; Satoto, Handy Febri (J-ENSITEC, 2024)
Pak Temmy Rahadi's Tempe UMKM is one of the tempe making UMKM located in Ds. Karangandong, Kec. Kedamean, Gresik. This UMKM was founded in 2010. Mr. Temmy Rahadi's tempe UMKM has a daily tempeh production target of 450 to 600 pcs and uses 80 kg to 100 kg of soybeans for daily production. The majority of customers are market middlemen, penyetan sellers, and home-based people in Kedamean, Gresik. In developing tempe MSMEs, there are various aspects that need to be considered to improve product quality and market competitiveness. One critical aspect is the tempeh packaging process, which plays an important role in ensuring product safety and quality. Currently, Mr. Temmy's tempeh MSMEs are facing significant problems related to the plastic hole punching tool for tempeh packaging which uses a knife in the process before packaging. The tool for punching plastic packaging using a knife requires a long processing time and also the results of the punching are not uniform, resulting in imperfect holes in the plastic packaging, thus making the tempe fermentation process less than optimal. Therefore, researchers are interested in raising this problem. By making a plastic hole punch tool for tempeh packaging, we hope that it will be able to improve the performance of tempeh production. In designing a plastic hole punch tool for tempeh packaging, researchers used ergonomic anthropometric approaches.